Effects of itraconazole and rifampicin on the single‐dose pharmacokinetics of the nonsteroidal mineralocorticoid receptor blocker esaxerenone in healthy Japanese subjects - Kirigaya, Yoshiaki; Shiramoto, Masanari; Ishizuka, Tomoko; Uchimaru, Hinako; Irie, Shin; Kato, Manabu; Shimizu, Takako; Nakatsu, Takafumi; Nishikawa, Yasuhiro; Ishizuka, Hitoshi (British journal of clinical pharmacology, 2020)
Aims To investigate the effects of the strong cytochrome P450 (CYP) 3A inhibitor itraconazole and the strong CYP3A inducer rifampicin on the pharmacokinetics of single‐dose esaxerenone, a nonsteroidal mineralocorticoid receptor blocker, in healthy Japanese subjects. Methods Two open‐label, single‐sequence, crossover studies were conducted in healthy Japanese males aged 20–45 years. In Study 1 (n = 20), subjects received a single oral 2.5 mg dose of esaxerenone (Days 1, 13), with itraconazole 200 mg twice daily (Day 8) and once daily (Days 9–16). In Study 2 (n = 12), subjects received a single oral 5 mg dose of esaxerenone (Days 1, 13), with rifampicin 600 mg once daily (Days 8–16). The plasma concentration of esaxerenone and esaxerenone metabolites were measured using liquid chromatography–tandem mass spectrometry. Pharmacokinetic parameters were calculated using noncompartmental analysis, and safety was assessed. Results Esaxerenone exposure increased when coadministered with itraconazole. Geometric least‐square mean ratios (90% confidence interval) of peak plasma esaxerenone concentration (Cmax), area under the plasma concentration–time curve (AUC) from zero until the last measurable concentration (AUClast) and AUC from zero until infinity (AUCinf) were 1.13 (1.05, 1.20) ng mL−1, 1.47 (1.40, 1.54) ng h mL−1 and 1.53 (1.45, 1.62) ng h mL−1, respectively. Esaxerenone exposure decreased when coadministered with rifampicin. Geometric least‐squares mean ratios (90% confidence interval) of esaxerenone Cmax, AUClast and AUCinf were 0.659 (0.599, 0.724), 0.315 (0.300, 0.332) and 0.312 (0.297, 0.328), respectively. Conclusion Itraconazole increased esaxerenone AUCinf by 53.1%, and rifampicin decreased esaxerenone AUCinf by 68.8%. These results suggest that caution is recommended when coadministering esaxerenone with strong inhibitors and inducers of CYP3A.